Triphenylphosphine Catalyzed Stereoselective N-Vinylation of N-(1,3-Dioxo-1,3-dihydroisoindol-2-yl)benzamide - RAMAZANI, ALI; GANJEIE, BIJAN (Asian Journal of Chemistry, 2010)
Protonation of the highly reactive 1:1 intermediates produced in the reaction between triphenylphosphine and methyl acetylenecarboxylate by N-(1,3-dioxo-1,3-dihydroisoindol-2-yl)-benzamide leads to vinyltriphenylphosphonium salt, which undergo an addition-elimination reaction in CH2Cl2 at room temperature to produce N-vinylated N-(1,3-dioxo-1,3-dihydroisoindol-2-yl)benzamide in good yield.